The Effect of Service Process on Guests Encounter Satisfaction at Three-Star Hotels - Mohd Ali, Hairuddin (2006)
Most studies on the hotel industry deal with customer satisfaction and service quality in general. However, this study focuses on encounter satisfaction during the check-in process at three-star hotels in Peninsular Malaysia. The objectives of the study are to examine the ten dimensions of perceptual filters (PF) of the service process that directly atlect guests encounter satisfaction (GEST) at the check-in process and to evaluate whether these PF components are indirectly affecting GEST through mediators referred to as situational descriptors (SD) of the service process. In addition, this study develops and examines a hypothesized model for any causal relationships. The Seven-point Likert scale survey instrument is used to collect data from 1,250 guests from thirty-five selected three-star hotels and the SPSS version 11.5 software is used to compute descripti\.e statistics, carry out factor analyses and reliability testing. AMOS -1.0 ih crnploycd for confirmatory factor analysis (CFA), model and hypotheses testing.Analyses 01' the lindinps show an overall good-fit with the revised and competing models of the study. Confirmatory Factor Analysis (CFA) confirms the three-factor solution for both revised and competing models. In addition, CFA also confirms that five indicators measure the PF and SD, while three indicators measure the GEST. The causal direct and indirect effects of the structural model are also determined. Two (H3 & H5) out of five research hypotheses are supported by the findings of the study. The findings of the study indicate that key attributes of frontline employees directly affect GEST at the check-in service process of three-star hotels covered in the study. The important attributes and qualities of front-line employees relevant for GEST are being kno~vledgeable of the required processes to ensure consistency of performance, possess empathy to inspire trust and confidence, being well groomed and possess the ability to articulate the guest's active role in the service delivery process. In addition, guests encounter satisfactions are increased when frontline employees have knowledge of cross-cultural sensitivities to fulfill guests' emotional satisfaction and when the safety of the guests is always ensured. An important finding of the study is that the cliche "value for money" does not always entice guests. Although the scope of this study is limited to only three-star hotels in Peninsular Malaysia and the total number of PF and SD dimensions are limited to ten and eight respectively, nevertheless, the results are applicable to all hotels in general. In conclusion, this study establishes that in order to achieve the organization's objective, the management of hotels has to ensure that the employees and customers are effectively managed.